Variance in a Second Language Pronunciation Quality - Zdena Kralova; Martin Krajcovic (Communications - Scientific letters of the University of Zilina, 2009)
The study assessed the relation between the overall degree of perceived foreign accent in non-natives’ English speech and a variety of factors. Five native speakers of English were asked to auditorily evaluate the samples of free English speech produced by each of 99 non-native talkers using the equal-appearing interval scale. The 5-point scale was used to rate each of the variables for each non-native speaker and the interclass correlation coefficients were calculated to identify the most important predictors of foreign accent.